Problematika Pengembangan Kreativitas Anak Melalui Pada TK Al-Quran dan Madrasah Diniyah Awaliyah Al-Mukhlisin - Sitanggang, Agnesia; Anggraini, Elya Siska; Syarefi, Fakhira Azzahra; Rambe, Luthfiah Amri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to identify obstacles in the development of early childhood creativity in TK Al-Quran & Madrasah Diniyah Awaliyah Al-Mukhlisin and formulate strategies to overcome these obstacles. Based on the results of observations and interviews, it was found that less varied teaching methods and limited aids were the main obstacles in honing children's creativity. Children tend to be less free to explore and express creative ideas, which has an impact on their low self-confidence.